The Effect of Self-Regulated Learning Modules on Academic Procrastination and Critical Thinking Skills of Primary School Teacher Education Students of UNS - Atmojo, Idam Ragil Widianto; Ardiansyah, Roy; Lestari, Endah Yuliana (Mimbar Sekolah Dasar, 2024)
This research aims to determine the effect of the self-regulated learning module on academic procrastination and critical thinking abilities among college students in the PGSD (Primary School Teacher Education) program at Universitas Sebelas Maret (UNS). This study follows an experimental design with a quasi-experimental approach. The research population comprises students enrolled in the PGSD program at UNS, with a sample size of 67 students. The sample group was divided into an experimental class and a control class. The experimental class consisted of 34 students from class 2E, while the control class comprised 33 students from class 2F. Content validity assessment using Aiken’s V confirmed the validity of all research instruments were valid. The reliability of the instruments, as measured by Cronbach’s Alpha coefficient, indicated their reliability, with a coefficient value of 0.833 for the academic procrastination scale and 0.713 for the critical thinking test. The hypothesis testing employed a Manova Test for Multivariate Analysis. The results demonstrate a significant simultaneous effect of self-regulated learning modules on academic procrastination and critical thinking skills among PGSD students at UNS, with a significance value (Sig.) in the Multivariate Test of 0.000, which is less than 0.05. These research findings can positively impact students by enhancing their understanding and application of self-regulation in learning—a crucial skill to develop. Moreover, the outcomes of this experimental research can motivate students to invest more effort in improving the quality of their learning experiences, leading to a reduction in academic procrastination levels and an enhancement of critical thinking skills.